Cost-effectiveness analysis of metformin and metformin-glimepiride in patients with type 2 diabetes at nene mallomo sidrap general hospital - Shabran Hadiq; Woro Supadmi; Dyah Aryani Perwitasari (Universitas Ahmad Dahlan, 2022)
Metformin and metformin-glimepiride are cost-effective therapy options and are most commonly prescribed to treat type 2 diabetes mellitus (DM). This study aims to determine the cost-effectiveness of using metformin and metformin-glimepiride in patients with type 2 DM at Nene Mallomo Sidenreng Rappang General Hospital. This analytical descriptive observational research employed a retrospective cohort design. The data of type 2 DM patients, new and old patients, were obtained from the medical record unit. The target population was data of outpatients for the period January-December 2019. The parameter of the therapeutic effectiveness is the random blood sugar levels of the patients after receiving treatment. The data on cost from the hospital perspective were obtained from the administration and finance unit. Cost-effectiveness analysis employed calculations of the average cost-effectiveness ratio (ACER) and the incremental cost-effectiveness ratio (ICER). Meanwhile, the risk ratio (RR) employed the analytical chi-squared method to determine the relationship between the two types of therapies and their effectiveness. This study has revealed that 30 patients met the inclusion criteria; 14 patients received metformin therapy and 16 patients received metformin-glimepiride therapy. Metformin therapy is more effective (64.29%) and more costly (IDR120,736). The metformin's ACER value is 1877.99, and its ICER value is -3107.26. The cost-effectiveness analysis has revealed that metformin therapy is more cost-effective than metformin-glimepiride therapy. Meanwhile, the chi-squared analysis has discovered no relationship between the two therapies and their effectiveness. The RR value of 1.080 concludes that metformin has 1.080 as much therapeutic effectiveness as the metformin-glimepiride.